2019
DOI: 10.4049/jimmunol.1800389
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae OmpU Mediates CD36-Dependent Reactive Oxygen Species Generation Triggering an Additional Pathway of MAPK Activation in Macrophages

Abstract: OmpU, one of the porins of Gram-negative bacteria Vibrio cholerae, induces TLR1/2-MyD88-NF-kB-dependent proinflammatory cytokine production by monocytes and macrophages of human and mouse origin. In this study, we report that in both the cell types, OmpU-induced proinflammatory responses involve activation of MAPKs (p38 and JNK). Interestingly, we observed that in OmpU-treated macrophages, p38 activation is TLR2 dependent, but JNK activation happens through a separate pathway involving reactive oxygen species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Macrophages infected with bacteria showed increased ROS generation [29]. To verify whether Oxi-αCD NPs can consume intracellular and extracellular hydrogen peroxide, the P727 isolate-infected RAW 264.7 cells were treated with blank PLGA NPs (non-ROS-responsive), blank Oxi-αCD NPs, MXF/Oxi-αCD NPs and MXF/FA-Oxi-αCD NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages infected with bacteria showed increased ROS generation [29]. To verify whether Oxi-αCD NPs can consume intracellular and extracellular hydrogen peroxide, the P727 isolate-infected RAW 264.7 cells were treated with blank PLGA NPs (non-ROS-responsive), blank Oxi-αCD NPs, MXF/Oxi-αCD NPs and MXF/FA-Oxi-αCD NPs.…”
Section: Resultsmentioning
confidence: 99%
“…ROS is known to be generated from several sources, including mitochondria and NADPH oxidase [ 67 ]. A previous study showed that ROS generated by both mitochondria and NADPH oxidase were involved in JNK activation in Vibrio cholerae OmpU-treated macrophages [ 68 ]. In our study, we also observed an involvement of ROS in H2-induced JNK activation and pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, upon attaching to host enterocytes, flagellin interacts with TLR5, prompting the production of IL-8 by activating p38, c-JNK, and Erk1/2 [135]. Similarly, OmpU, another extracellular protein primarily functioning as a porin, activates proinflammatory responses by activating p38 and c-JNK MAPKs through the TLR2 receptor [136].…”
Section: Vibrio Cholerae and Vibrio Parahaemolyticusmentioning
confidence: 99%